PENGARUH TERAPI RELAKSAS IOTOT PROGRESIF TERHADAP PERUBAHAN TINGKAT INSOMNIA PADA LANSIA DI PUSKESMAS ONGKAW SINONSAYANG KABUPATEN MINSEL - Rugian, Indri (Journal Of Community & Emergency, 2024)
Advanced (elderly) is the final period in human life where a person begins to experience changes marked by physical, psychological and social changes, resulting in a decrease, inhibition, vulnerability to disease, environmental changes, and physiological changes that occur. Research: The purpose of this study was to determine the effect of progressive muscle relaxation therapy on changes in insomniaResearch Methods: This type of research is a quantitative study with a pre-experimental research design with a "one group pretest-posttest" design, without a comparison (control) group. This study uses the pretest-posttest method. This research has been carried out on respondents in the Ongkaw Sinonsayang Health Center, Minsel, from May to June 2022. The population in this study is the community in the working area of the Ongkaw Sinonsayang Public Health Center as many as 35 respondents. The sampling technique in this study is purposive samplingThe results of this study are the variables of diet and the incidence of gastritis by using the Chi Square test there is an effect of progressive muscle relaxation with Insomnia in the Elderly. Statistical test results obtained p value = 0.000, so that there can be a significant effect locking between progressive muscle relaxation therapy and changes in elderly insomnia, s Ha is accepted, Ho is rejected.The conclusion is that elderly insomnia at the Ongkaw Sinonsayang health center in South Sumatra generally experienced a decrease from severe to mild. Respondents in the work area of the Ongkaw Sinonsayang Health Center generally experience insomnia. There is an effect of progressive muscle relaxation therapy on changes in insomnia in the elderly at the Ongkaw Sinonsayang Minsel Public Health Center. Suggestions for the Ongkaw Health Center It is hoped that it can provide information or advice to patients for good muscle relaxation therapy and in order to maintain good sleep patterns to reduce changes in the elderly